Los payasos: carnaval y patrimonio barveño - Salas Núñez, Gabriela (2013)
This article enrolls the festivals that take place in honor of the Patron Saint of Barva inside to carnival, as Bakhtin understands, it means, like an experience, a party where all the people involved. In the course of the festival can only be lived according with its laws, that is, there is total freedom to act in this new order.